Incentive Mechanism of R&D Firms’ Collaborative Innovation Based on Organisational Ambidexterity - Bo Song; Penghao Jin; Liangjie Zhao (Discrete Dynamics in Nature and Society)
From the perspective of organizational ambidexterity, we consider the choice of innovation strategy among R&D firms. By building on contractual arrangements and employing a dynamic game model, we focus on the incentive mechanism of R&D Firms’ collaborative innovation and analyze incentive contracts of benefits distribution and cost-sharing when two firms conduct market-driven innovation (exploitative innovation) strategy and technological research-driven innovation (exploratory innovation) strategy respectively, and collaborate for innovation with each other. We also discuss the influence of exploratory and exploitative innovation effects on decision-making of R&D firms regarding whether to choose collaborative innovation under different incentive contracts. The results show that the effects of exploratory innovation acts as the intrinsic motivation of collaborative innovation while exploratory innovation could be improved to some degree by exploitative innovation. In addition, both investment levels of exploratory and exploitative innovation would decrease (increase) when innovation cost (innovative efficiency) increases. Moreover, compared with a benefit-distribution contract, cost-sharing contracts would not only lead exploitative innovation to realize optimal revenue, but also provide incentives for exploratory innovation more effectively.